Effectiveness of Water Extract of Sea Lettuce (Ulva Lactuca) from Aceh to Reduce Blood Glucose Levels in Diabetic Rats - Rinawati Rinawati; Sri Wahyuni Muhsin; Hanif Muchdatul Ayunda (Journal of Nutrition Science, 2022)
Diabetes mellitus (DM) is a non-communicable disease characterized by high blood glucose levels caused by damage to the pancreas, which cannot produce insulin. Antidiabetic drugs and insulin injections in the long term have specific side effects, so herbal medicine is considered safer to use. Sea lettuce (Ulva lactuca) is one of the herbal medicines that have the potential as an antidiabetic. Methods: Experimental using a completely randomized design. Rats were divided into five groups with three replicates, namely: Kn = normal control, Ka = STZ control, P1 = DM rats + 200 mg/KgBB extract dose, P2 = DM rats + 300 mg/KgBB extract dose, and P3 = DM rats + 400 mg/KgBB extract dose. The stages of this study began with the preparation of tools and materials, phytochemical tests, the preparation of test animals and testing extracts on test animals, and the measurement of blood glucose levels in rats before and after they were given extracts. Blood glucose levels were measured using a glucometer. Data analysis was performed statistically (ANOVA). The results of the phytochemical tests detected were steroids, saponins, and phenols/tannins, while alkaloids, terpenoids, and flavonoids were not. The most effective blood glucose level measurement result is at a dose of 400 mg/KgBB.